Seasonal movements and distribution of the Spectacled Eider - Dau, C P; Kistchinski, S A (Wildfowl, 1977)
Observations show that the nesting patterns of the Spectacled Eider, Somateria fischeri are similar on their Alaskan and Siberian nesting areas. Adult males are the first to leave the nesting grounds, doing so during the incubation period. Subadult males are rarely encountered on the nesting grounds and but few subadult females. Seasonal movements to and from the nesting grounds are poorly known. Published and unpublished data on the distribution in fall and winter are summarized and interpreted in conjunction with information on the dynamics of the Bering Sea ice pack as revealed by Satellite photographs.